Perceived barriers to accessing mental health services among black and minority ethnic (BME) communities: a qualitative study in Southeast England. Issue 11 (16th November 2016) - Memon, Anjum; Taylor, Katie; Mohebati, Lisa M; Sundin, Josefin; Cooper, Max; Scanlon, Thomas; de Visser, Richard
Abstract : Objective: In most developed countries, substantial disparities exist in access to mental health services for black and minority ethnic (BME) populations. We sought to determine perceived barriers to accessing mental health services among people from these backgrounds to inform the development of effective and culturally acceptable services to improve equity in healthcare. Design and setting: Qualitative study in Southeast England. Participants: 26 adults from BME backgrounds (13 men, 13 women; aged >18 years) were recruited to 2 focus groups. Participants were identified through the registers of the Black and Minority Ethnic Community Partnership centre and by visits to local community gatherings and were invited to take part by community development workers. Thematic analysis was conducted to identify key themes about perceived barriers to accessing mental health services. Results: Participants identified 2 broad themes that influenced access to mental health services. First, personal and environmental factors included inability to recognise and accept mental health problems, positive impact of social networks, reluctance to discuss psychological distress and seek help among men, cultural identity, negative perception of and social stigma against mental health and financial factors. Second, factors affecting the relationship between service user and healthcare provider included the impact of long waiting times for initial assessment, language barriers, poor communication between service users and providers, inadequate recognition or response to mental health needs, imbalance of power and authority between service users and providers, cultural naivety, insensitivity and discrimination towards the needs of BME service users and lack of awareness of different services among service users and providers. Conclusions: People from BME backgrounds require considerable mental health literacy and practical support to raise awareness of mental health conditions and combat stigma. There is a need for improving information about services and access pathways. Healthcare providers need relevant training and support in developing effective communication strategies to deliver individually tailored and culturally sensitive care. Improved engagement with people from BME backgrounds in the development and delivery of culturally appropriate mental health services could facilitate better understanding of mental health conditions and improve access.